2008
DOI: 10.1523/jneurosci.3632-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fluoxetine Stimulates Maturation and Synaptic Plasticity of Adult-Born Hippocampal Granule Cells

Abstract: Chronic treatments with selective serotonin reuptake inhibitors (SSRIs) have been shown to increase hippocampal neurogenesis. However, it is not known whether SSRIs impact the maturation and functional integration of newborn neurons. Here we examined the effects of subchronic and chronic fluoxetine on the structural and physiological properties of young granule cells. Our results show that doublecortin-positive immature neurons displayed increased dendritic arborization after chronic fluoxetine treatment. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
457
6
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(504 citation statements)
references
References 39 publications
40
457
6
1
Order By: Relevance
“…We have seen these effects of repeated testing routinely. For example, in the NSF paradigm, the latency to feed was decreased after a second exposure to the test (Wang et al, 2008). In the present study, we observed a decrease in the time spent in the center of the arena owing to the re-exposure to the test in all treated groups.…”
Section: The Rapid Anxiolytic and Antidepressant-like Effects Of A Susupporting
confidence: 60%
“…We have seen these effects of repeated testing routinely. For example, in the NSF paradigm, the latency to feed was decreased after a second exposure to the test (Wang et al, 2008). In the present study, we observed a decrease in the time spent in the center of the arena owing to the re-exposure to the test in all treated groups.…”
Section: The Rapid Anxiolytic and Antidepressant-like Effects Of A Susupporting
confidence: 60%
“…A recent study showed that fluoxetine, known to enhance the proliferation of early progenitors cells in the adult brain (Encinas et al, 2006), also increases the maturation and survival of newborn neurons at 21 days post-BrdU (Wang et al, 2008). Here, we found that agomelatine appeared to induce an early acceleration of cell maturation at 8 days of development.…”
Section: Adult Neurogenesis and Antidepressantsupporting
confidence: 52%
“…Over the past decade, the field of adult hippocampal neurogenesis has seen significant work. The region has attracted much interest since newborn neurons in the SGZ contribute to enhanced neural plasticity that can sustain specific brain functions [1][2][3][4][5] . Adult hippocampal neurogenesis has been implicated to play important roles in mood regulation, regeneration, and learning and memory.…”
Section: Introductionmentioning
confidence: 99%